Neuronavigation-assisted stereotactic minimally invasive puncture with tenecteplase for the treatment of acute spontaneous deep intracerebral haemorrhage (NAS-TNK): rationale and design of a multicentre randomised trial - Duolao Wang; Yong Cao; Shaozhi Zhao; Pengqi Wang; Mingze Wang; Zhiyou Wu; Jingyi Tang; Xiudan Bai; Yang Ni (Stroke and Vascular Neurology)
Introduction Minimally invasive puncture surgery followed by thrombolysis has been proven to be an effective approach for managing hypertensive intracerebral haemorrhage (ICH). Nevertheless, its impact on improving neurological outcomes remains controversial. The integration of neuronavigation-assisted stereotactic (NAS) technology will significantly help enhance the accuracy of catheter placement, while tenecteplase (TNK), a third-generation thrombolytic agent, offers stronger capabilities in breaking down platelet-rich clots and demonstrates increased fibrin selectivity, which could enhance the overall effectiveness of thrombolytic treatment. However, the efficacy and safety of combining NAS-assisted minimally invasive puncture with TNK (NAS-TNK) in reducing disability and mortality rates among patients with acute spontaneous deep ICH remain unknown.Aim To describe the rationale and design of the NAS-TNK trial for the treatment of acute spontaneous deep ICH.Design NAS-TNK is a randomised, open-label, outcome-blinded multicentre trial, involving 732 participants with acute basal ganglia or thalamic haemorrhage with a haematoma volume ranging from 20 to 50 mL. This study will evaluate the efficacy and safety of NAS-TNK, administered every 24 hours at a dose of 0.009 mg/mL of haematoma volume, compared with participants receiving standard medical care. Each patient will undergo follow-up evaluations for a period of 180 days.Study outcomes The main measure of effectiveness is the percentage of participants achieving a modified Rankin Scale Score ranging from 0 to 3 at the 180-day mark. The primary safety outcome is the all-cause death at 30 days.Discussion and conclusion The NAS-TNK study will help improve our understanding of the benefits of NAS-TNK in patients with acute spontaneous deep ICH.